Development and validation of the Bullying and Cyberbullying Scale for Adolescents: A multi‐dimensional measurement model. (3rd May 2018) - Thomas, Hannah J.; Scott, James G.; Coates, Jason M.; Connor, Jason P.
Abstract : Background: Intervention on adolescent bullying is reliant on valid and reliable measurement of victimization and perpetration experiences across different behavioural expressions. Aims: This study developed and validated a survey tool that integrates measurement of both traditional and cyber bullying to test a theoretically driven multi‐dimensional model. Sample: Adolescents from 10 mainstream secondary schools completed a baseline and follow‐up survey ( N = 1, 217; M age = 14 years; 66.2% male). Methods: The Bullying and cyberbullying Scale for Adolescents (BCS‐A) developed for this study comprised parallel victimization and perpetration subscales, each with 20 items. Additional measures of bullying (Olweus Global Bullying and the Forms of Bullying Scale [FBS]), as well as measures of internalizing and externalizing problems, school connectedness, social support, and personality, were used to further assess validity. Results: Factor structure was determined, and then, the suitability of items was assessed according to the following criteria: (1) factor interpretability, (2) item correlations, (3) model parsimony, and (4) measurement equivalence across victimization and perpetration experiences. The final models comprised four factors: physical, verbal, relational, and cyber. The final scale was revised to two 13‐item subscales. The BCS‐A demonstrated acceptable concurrent and convergent validity (internalizing and externalizing problems, school connectedness, social support, and personality), as well as predictive validity over 6 months. Conclusions: The BCS‐A has sound psychometric properties. This tool establishes measurement equivalence across types of involvement and behavioural forms common among adolescents. An improved measurement method could add greater rigour to the evaluation of intervention programmes and also enable interventions to be tailored to subscale profiles.